Solutions to Enhance the Quality of Domestic Tour Services for Local Customers at NonNuocViet Trade and Service Travel Company Limited - Trinh, Thuc Ngan (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Major in Digital Travel and Tourism Services Management